Simulated effects of climate change on green gram production in Kitui County, Kenya - Mugo, Jane Wangui; Opijah, Franklin J.; Ngaina, Joshua; Karanja, Faith; Mburu, Mary (Frontiers in Sustainable Food Systems, 2023)
This study purposed to evaluate the impact of climate change on green gram yield, biomass and days to maturity under the baseline and future climate scenarios in Kitui County, Kenya, a highly suitable region for green gram production. The datasets utilised in this study were the daily observed and simulated rainfall, maximum and minimum temperature, and solar radiation during the March-April-May (MAM) and October-November-December (OND) planting seasons. The observed parameters were obtained from the South Eastern Kenya University (SEKU) farm weather station, and simulated daily data were from the equal-weight ensemble of the CORDEX RCA4 model. Data on soil and green gram phenology were used to calibrate the APSIM green gram model for four varieties of green gram, namely Biashara, Tosha, N26, and KS20 varieties. The calibrated green gram model captured the observed yield, biomass and days to maturity of the four varieties of green gram shown by a coefficient of determination which ranged between 87.0% and 99.0%; bias values which ranged between 1.3 and 25.3 and levels of NRMSE which ranged between 4.7% and 45.5%. During the MAM and OND seasons, a statistically significant decline in yield, biomass, and days to maturity is expected under both the RCP 4.5 and RCP 8.5 scenarios. The high variability in rainfall amount under both the RCP 4.5 and RCP 8.5 scenarios will translate to a lower yield and biomass. The increase in temperature under both the RCP 4.5 and RCP 8.5 scenarios will reduce the days to maturity for green grams in Kitui County. A decline in green gram yield is expected under future climate scenarios in one of the highly suitable zones for Kitui County, Kenya. Given that the government aims to revive farming in the ASALs by promoting climate-smart agriculture through planting drought-resistance crops, there is a need to develop green gram varieties which are more tolerant to the expected increase in temperature and rainfall variability to increase yield and in turn benefit farmers, the society and the country at large.